Factors of (dis)satisfaction with body self-image in adolescence - Guilherme, José Francisco Nunes; Martins, Carla Alexandra Ramalho de Sena; Nunes, Maria Cristina de Oliveira Salgados; de Jesus, Saúl Neves (Seven Editora, 2024)
In adolescence, young people have to adapt to almost radical transformations, being the (dis)satisfaction with body self-image a reality.The aim of this research is to determine the relationship between physical condition and (dis)satisfaction with body self-image. To know how (in)satisfaction with body self-image relates to male versus female and analyse the association with academic achievement at a global level, according to gender and age. Participated 1517 adolescents, 701 males (46.18%), aged between 12 and 17 years.The physical condition was assessed by Fitnessgram, the (dis)satisfaction with body self-image, using the Collins Silhouette Scale (1991), was adapted by Simões (2014), and the academic performance by the arithmetic average of the curriculum subjects.There was a statistically significant relationship between (dis) satisfaction with body self-image and physical fitness level groups in the global sample and in males.The associations between body image (dis)satisfaction and academic achievement, global, male, and female gender, are not significant (p < 0.05). Between age and (in)satisfaction with body self-image globally and in women, the correlations are negative, significant, and weak. DOI:https://doi.org/10.56238/sevened2024.015-017